THE ANALYSIS OF CODE MIXING ON STUDENTS’ FACEBOOK: A STUDY ON FACEBOOK STATUS AND COMMENTS OF THE SIXTH SEMESTER STUDENTS TBI IAIN PADANGSIDIMPUAN - Laila Safitri; Eka Sustri Harida; Hamka Hamka (English Language Teaching and Research, 2017)
The aim of this research was to find code mixing on students’ facebook that posted on facebook status and comments of the sixth semester TBI IAIN Padangsidimpuan. The facebook users often mixed their language with another language in status and comments on facebook. The objectives of this research were to find out of the use of code mixing, types of code mixing and students reasons in using code mixing on facebook status and comments in English Education Program at TBI-1 Sixth Semester. To answer the objectives of the research, the researcher used descriptive qualitative method. The results of the data analysis showed three types of code mixing suggested by Muysken such as insertion, alternation and congruent lexicalization, appeared in Facebook. There were amounts of code mixing that had been done by facebook user or sixth semester students TBI-1 were 71 for insertion, 9 times for alternation and 3 for congruent lexicalization. So, the total of code mixing that had been done by them was 83 times. Insertion code mixing was more often use than alternation and congruent lexicalization code mixing in facebook users status and comments posted. It could be seen from this percentages, they used 3.61 % insertion, while alternation 85.54% and 10.85% congruent lexicalization. So, the facebook users were dominantly used insertion than alternation and congruent lexicalization. Moreover, the reasons of doing the codes were so varieties, such as would improve their language, mixing some language was unique, could not say and forgot the word, live in bilingual environment, to make emphasize, funny, joke, and applying new words on facebook status and comments. Keywords: Code Mixing, Facebook, Status, Comments